A PUBLIC VALUE PERSPECTIVE ON DEVELOPING PUBLIC SECTOR PROJECTS: PENANG MASS TRANSPORT - Akshay Bagde; Ramona Blanes; Salmi Mohd Isa, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The effects on climate change and environment, sustainability in transportation should be the primary goal of every transportation systems. The city of Penang is failing to cope with the old transportation infrastructure due to the rapid economic growth and the boost of migration for work. The involvement of stakeholders in the deliverance of mass transport services is necessary to meet public needs. The findings from the case study reveal that Penang is in an acute need for a well-connected and robust sustainable transport system. The current structure of creating government policies is inadequate for the handling of the congestion along with policies it needs integration of the transport systems with rail systems. The authors propose that the adoption of a Public Value measurement framework can significantly improve the desired outcomes. The framework enables public managers to understand the needs of citizens and deliver a right balance of infrastructure development and amendments needed in policy that can help Penang achieve a value-based sustainable transportation system.